2021
DOI: 10.3389/fmicb.2021.750089
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk of DNA Methylation Triggered by Pathogen in Poplars With Different Resistances

Abstract: DNA methylation plays crucial roles in responses to environmental stimuli. Modification of DNA methylation during development and abiotic stress responses has been confirmed in increasing numbers of plants, mainly annual plants. However, the epigenetic regulation mechanism underlying the immune response to pathogens remains largely unknown in plants, especially trees. To investigate whether DNA methylation is involved in the response to infection process or is related to the resistance differences among poplar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 69 publications
(115 reference statements)
0
11
0
Order By: Relevance
“…In accordance with that, global methylation presented a lower increase in the tolerant genotype. Analysis of global DNA methylation pattern modification on several species after infection with different pathogens has been reported on tomato roots, Poplar bark and Arabidopsis leaves (Leonetti & Molinari, 2020 ; Xiao et al, 2021 ). Often, resistant species showed DNA hypomethylation patterns while susceptible ones presented hypermethylated DNA after pathogens attack (Leonetti & Molinari, 2020 ; Xiao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with that, global methylation presented a lower increase in the tolerant genotype. Analysis of global DNA methylation pattern modification on several species after infection with different pathogens has been reported on tomato roots, Poplar bark and Arabidopsis leaves (Leonetti & Molinari, 2020 ; Xiao et al, 2021 ). Often, resistant species showed DNA hypomethylation patterns while susceptible ones presented hypermethylated DNA after pathogens attack (Leonetti & Molinari, 2020 ; Xiao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of global DNA methylation pattern modification on several species after infection with different pathogens has been reported on tomato roots, Poplar bark and Arabidopsis leaves (Leonetti & Molinari, 2020;Xiao et al, 2021). Often, resistant species showed DNA hypomethylation patterns while susceptible ones presented hypermethylated DNA after pathogens attack (Leonetti & Molinari, 2020;Xiao et al, 2021). Also, studies have observed that altering DNA methylation levels (hypo-or hypermethylation) on genomic regions could influence gene and phenotypic responses to plant diseases (Geng et al, 2019;Leonetti & Molinari, 2020) Wang, 2015;Espinas et al, 2016;Ramirez-Prado, Piquerez, et al, 2018;Song et al, 2021;Wang et al, 2020;Zhi & Chang, 2021).…”
Section: Dna Methylation Plays a Role In The Plant Immune Defence Systemmentioning
confidence: 99%
“…The dynamics of DNA methylation play important roles in the epigenetic regulation of plant growth, development, and response to environmental stresses [116]. For instance, several studies have revealed the potential role of DNA methylation in flower development [117], drought tolerance [118], wood formation [119], and immune response to pathogen infection [120] in Populus species. Since DNA methylation alters gene expression, transcriptome analysis is usually combined with methylation analysis to investigate the functional relationship between the epigenome and transcriptome [114].…”
Section: Epigenomicsmentioning
confidence: 99%
“…Demethylation of promoters leads to cis elements being more accessible to TFs, ultimately leading to increased NLR gene expression and disease resistance. In poplar trees infected with Lonsdalea populi , hypomethylation occurred at CH sites within promoter regions of defense-related genes ( Xiao et al, 2021 ). Higher levels of hypomethylation were particularly noted in poplar trees with increased resistance toward L. populi when compared to susceptible trees.…”
Section: More Is Better—sometimes: Nlr Expressionmentioning
confidence: 99%